Incidence of dengue in the Islands - Rao, Shivani; Sethuraman, Ajay Raj; Thatkar, Pandurang Vithal (International Journal Of Community Medicine And Public Health, 2020)
Background: Dengue is transmitted mainly by bite of Aedes mosquito namely Aedes aegypti and Aedes albopictus posing major public health concern. The objective of the study is to study incidence of dengue in Andaman and Nicobar Islands. Methods: Prospective study from January 2012 to December 2018 from all primary, community and tertiary health centres of Andaman and Nicobar Islands. Results: Out of a total of 5255 blood samples tested from 2012 to 2018 the total dengue positive cases were 525 (9.99%). Conclusions: There has been gradual increase in number of dengue cases from 2012 to 2016 thereafter there has been reduction of cases.